A New Electoral system for Ireland? - Laver, Michael (Trinity College Dublin, 1998)
A New Electoral system for Ireland? looks at the possibility of doing away with the current Single Transferable Vote electoral system in Ireland. It explores the impact of replacing STV with an alternative widely favoured by electoral reformers, the 'additoinal member' system used for example in Germany and New Zealand. It looks at the potential impact of such a system on both competition between parties and the competition within parties that many Irish politicians regard as a corrosive feature of STV.
Keywords: Public Policy; Electoral reform; Ireland